Perception of Families With Family Attitudes About Mental Disorders in Family Members That Experience Mental Disorders in The Mental Hospital - Andriana, Kiki Rizki Fista; Yunus Adi Wijaya (Basic and Applied Nursing Research Journal, 2021)
Mental disorders are considered as incurable diseases and are related to sin or crime, so that sometimes the treatment is brutal and inhumane. Wrong perceptions or myths related to mental disorders (schizophrenia) still exist in Indonesia; some cultural societies always link the cause of mental disorders caused by the occult. This perception causes them to come to health or mental health services if the mental disorder they experience is severe or even disturbs others. This study aims to determine the perception of families with family attitudes about mental disorders in family members that experience mental disorders in the mental hospital. Analytical research with cross sectional approach. Using 67 respondents with consecutive sampling probability sampling technique. Spearman rank's analysis results obtained p (0.00) <0.05 (0.000) with a correlation coefficient of 0.752, which shows the closeness of the relationship between the variable perception with attitude is strong. The conclusion of the study, there is a relationship between the perception of families with family attitudes about mental disorders in family members that experience mental disorders in the mental hospital.